KUNYIT ASAM AND SINOM BEVERAGES INHIBITION WITH ?-GLUCOSIDASE ENZYME ACTIVITY - Adi Widari, Ida Ayu; Mulyani, Sri; Admadi H, Bambang (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 2 No 2 (2014): September)
Kunyit asam and sinom are the kinds of Indonesian traditional beverage, which have a potency to be developed as a source of antioxidant. The research was carried out to determine the antioxidant capacity of kunyit asam and sinom beverages and their inhibition activity against ?-glucosidase. Antioxidant capacity was analyzed using DPPH (1,1-diphenyl-2-picrylhydrazyl) method. Regression method was used to find out the correlation between the antioxidant capacity of the beverage and percentage of inhibited ?-glucosidase The result showed that antioxidant capacity of both beverages correlated significantly with the percentage of ?-glucosidase inhibition. Antioxidant capacity of kunyit asam beverage was 2.04 mg GAEAC/g (2,042 ppm) and its IC50 was about 146.48 ppm against the activity of ?-glucosidase. Sinom beverage had antioxidant capacity of 1.88 mg GAEAC/g (1,881 ppm) and its IC50 was 231.37 ppm. Keywords : kunyit asam, sinom, antioxidant, inhibition, and ?-glucosidase
Keywords: 18,